Aplicación móvil intérprete entre personas con discapacidad visual y auditiva a partir de técnicas de procesamiento de lenguaje natural - Carrillo Vélez, Edison Steven (2016)
People with hearing and visual impairment Educational Specialized Unit of Cotopaxi, since 2014 to make the process of communication in their environment and outside it, they use other people as a communication channel, which leads to dependence on others and if there is no person to serve as a channel you cannot start a conversation, causing low self-esteem limiting their actions, thereby preventing the fulfillment of their needs for affiliation. Consequently this project is the development of a mobile application interpreter in the Android operating system, to facilitate communication between a hearing impaired person and a person with visual impairment of the Special Education Unit of Cotopaxi city of Latacunga, by processing techniques that are natural language interactions between machines and human language is written or spoken.